(untitled) (Biosaintifika: Journal of Biology & Biology Education, 2024)
Chronic lead exposure induces ROS accumulation which causes physiological disorders. Chelation therapy has been widely used to overcome lead poisoning since it exerts only a few side effects. Nano chitosan prevents lead poisoning by inhibiting ROS. This study examined the pharmacokinetics of nano chitosan in chronic lead-induced toxicity animal models and the mechanism of action pathway using the bioinformatic approach, The area under the curve was estimated to be 12110.13 ± 7709.37 μg/mL hours using the pharmacokinetic model, and the Cmax was 82.34 ± 5.64 μg/mL. The Tmax and t½ calculations were 22.68 ± 11.67 and 80.47 ± 60.58 hours respectively. Chitosan nanoparticles regulated VEGFA, FGF2, and LGALS3 which plausibly played a substantial role in chronic lead exposure. However, chitosan is not suitable for oral administration due to its low gastrointestinal solubility. These characteristics make chitosan nanoparticles have the prospect of being developed as a supplement so that they can contribute to overcoming the negative impacts of chronic lead poisoning.